Analysis of Additional Time Costs Construction of the Religious Court Office Building of Trenggalek Regency, East Java - Widyaningsari, Nidya; Tjendani, Hanie Teki; Sajiyo, Sajiyo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study discusses several ways to accelerate the building construction process. The study used two methods, namely crashing and overlapping. The crashing method involves adding overtime hours and labor to shorten the project duration. Meanwhile, overlapping is rearranging the relationship between tasks so that they can be done simultaneously without reducing the initial time, thus accelerating completion at a relatively comparable cost. The analysis results show that both methods are effective in accelerating projects, with the overlapping method requiring less cost and providing greater time reductions. The choice of the best method depends on budget constraints and the project's completion time requirements. Thus, this acceleration strategy can help project management in achieving time targets at an optimal cost.